Image and Incarnation in Pauline Christology: A Search for Origins - Lacey, Douglas R. de (Tyndale bulletin, 1979)
An examination of how one particular early Christian – the apostle Paul – came to grapple with the problem of understanding how a man could be considered worthy of worship.